(3HfGA fXGe ddJdNjU GdBdi ddfUhU GdYQHjI (B/ s - (3QbjI EHQGgje oeM`nqeOs; (3EHQGgje GdOShbj (B: s; (3GdeYJR HGddg GdnqSYjO (B: s ((3GdbGgQI (B: s (3QbjI EHQGgje oeM`nqeO (B: s, 2019)
(3ehVhY GdHMK gh (B"(3HfGA fXGe ddJdNjU GdBdi ddfUhU GdYQHjI(B": (3h jJchf GdHMK ef aUdjf(B: (3GdaUd GdChd ojbOe fXQI YGeI Ydi GdJdNjU GdBdi(B: (3h jJchf ef CQHYI eHGMK; GdeHMK GdChd ebOeI Yf GdJfbjH ai GdfUhU (B((3JYQjag h CgejJg h GdeLGdGJ GdeJUdI Hg h JWHjbGJg(B): (3h GdeHMK GdKGfi ojbOe eaGgje CSGSjI Yf GdJdNjU GdBdi (B((3JYQjag h CgejJg h CfhGYg h JWHjbGJg(B): (3h GdeHMK GdKGdK ojbOe efGgL GdJdNjU GdBdj(B: (3hGdeHMK GdQGHY njYpQV CSGdjH Jbjje GdedNUGJ GdBdjI(B. (3GdaUd GdKGfi gh eMGhdI dHfGA fXGe ddJNjU GdBdi ddfUhU GdYQHjI(B: (3h jJchf ef CQHYI eHGMK; GdeHMK GdChd jbOe eaGgje CSGSjI Yf GdeOhfGJ (B((3JYQjagG h CfhGYgG h NUGFUgG h GSJNOGeGJgG(B): (3h GdeHMK GdKGfi gh efgL GdHMK(B: (3h GdeHMK GdKGdK jbOe fJGFL GdHMK(B: (3h GdeHMK GdQGHY jYQV fehPL JWHjbi dfJGFL GdHMK(B. (3cGf GdgOa ef GdHMK gh hVY bhGYO dZhjI ojYJneO YdjgG ai HfGA fXGe ddJdNjU GdBdi ddfUhU(B: (3h bO GYJeOJ gPg GdbhGYO Ydi MPa GdYHGQGJ Ch GdLed GdJi dG Jfbd eYfi CSGSkjG(B: (3h oWpqHbJ gPg GdbhGYO Ydi eOhfI (B-(3echfI ef ebGdGJ ef ehShYI h jcjHjOjG (B- (3ddJMbb ef eOi LhOJgG(B. (3hJhUd GdHMK Edi Cf GdCLRGA (B((3GdeYdheGJ(B) (3GdJj ojecf MPagG ef GdfU HOhf GdJCKjQ Ydi LhOI eG JHbi efg (B((3GdedNU(B) (3gi GdCLRGA GdJj oJbOe(B: (3JaUjkdG(B- (3EVGaI(B- (3JYdjkdG(B- (3JNUjkUG (B- (3cjajI GdbjGe HGdaYd (B- (3Ref hbhY GdaYd(B. (3h de jcf ef Gdeecf MPa cd GdcdeGJ GdETGQjI GdJj oJbOe GdeYdheGJ GdSGHbI(B: (3h dcf Jenqcf GdHMK ef GdhUhd Edi Cf HYV gPg GdcdeGJ GdETGQjI Ohf ZjQgG jecf MPagG Ohf GdJCKjQ Ydi eYfi GdfU h UMJg GdfMhjI(B. (3h HGdEVGaI Edi Pdc hVY GdHMK eLehYI ef GdTQhW GdJj jLH JhGaQgG YfO MPa gPg GdCLRGA ef GdfU; h Pdc ddMUhd Ydi CaVd fJjLI eecfIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe Yde GdoqdZI h GdOQGSGJ GdSGejI h GdTQbjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdfUhU GdYQHjIs; (3CfhGY GdedNUGJs; (3fXGe ddJdNjU GdBdi s